Design of pressure vessels by stress analysis according to advanced design codes - Cheung, John S. T. (2008)
The main purpose of pressure vessels is to contain fluids under pressure. Safety during operation is of crucial importance since accidents can have serious destructive consequences. This is not only because of the built-up pressure energies in their fluid contents. It is also because the industrial processes often require the vessels to be subjected to high temperature, and/or to contain flammable and hazardous liquids and gases. In the early decades of the 20th century, arising from a number of serious accidents during the operations of pressure vessels, especially steam boilers, engineering communities in the USA and some European countries, got together to draft and issue pressure vessel codes of practice for the guidance of and often for compliance by plant operators. These pressure vessel codes once issued have to be regularly updated and upgraded by competent committees, very often based on results of further experience, and relevant investigations and research.